Enfermedades respiratorias del suino. Parte I : virus respiratorios. Revisión de literatura (1999)
ABSTRACT: The increasing incidence and severity of respiratory diseases in last years have been a complaining of Colombian producers. Four viruses and their diseases are discussed. Those are the Porcine Reproductive and Respiratory Syndrome virus-PRRSV, the Aujeszky's disease virus-ADV, swine Influenza virus-SIV (H1N1, H3N2), the Porcine Respiratory Coronavirus-PRCV and Porcine Circuvirus-PCV. The Porcine Cytomegalovirus is not included. Respiratory cases get complicated because of the concurrent respiratory viral and bacterial infections in the swine population. To date, except PRCV and PCV, the circulation of these viruses have been detected by serology and virus isolation by the government at the central diagnostic veterinary laboratory at Bogota (ICA-CEISA). Word wide, only Aujeszky disease; there is agreement the control measures, vaccines and vaccination programs.